2024
DOI: 10.1002/anie.202404885
|View full text |Cite
|
Sign up to set email alerts
|

An Indocyanine Green‐Based Nanoprobe for In Vivo Detection of Cellular Senescence

Andrew G. Baker,
Muhamad Hartono,
Hui‐Ling Ou
et al.

Abstract: There is an urgent need to improve conventional cancer‐treatments by preventing detrimental side effects, cancer recurrence and metastases. Recent studies have shown that presence of senescent cells in tissues treated with chemo‐ or radiotherapy can be used to predict the effectiveness of cancer treatment. However, although the accumulation of senescent cells is one of the hallmarks of cancer, surprisingly little progress has been made in development of strategies for their detection in vivo. To address a lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…(a) Synthesis and characterization: A recent study by Baker et al. revealed that the previously described methods resulted in the formation of additional side products together with ICG-Jagg; thus, ultracentrifugation is needed to separate/purify these Jagg from other side products . Moreover, their research revealed that Jagg primarily consist of ICG dimers rather than monomers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(a) Synthesis and characterization: A recent study by Baker et al. revealed that the previously described methods resulted in the formation of additional side products together with ICG-Jagg; thus, ultracentrifugation is needed to separate/purify these Jagg from other side products . Moreover, their research revealed that Jagg primarily consist of ICG dimers rather than monomers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ICG-Jagg have been employed for in vivo monitoring of cellular senescence through fluorescence and PAI . Jagg were found to be internalized by active endocytosis and exhibited selective accumulation within the lysosomal compartment in various in vitro cellular senescence models (Figure ).…”
Section: Applications Of Icg-jaggmentioning
confidence: 99%
See 1 more Smart Citation